2020
DOI: 10.3960/jslrt.20019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of genomic aberrations in adult T-cell leukemia/lymphoma

Abstract: Adult T-cell leukemia/lymphoma (ATL) is an aggressive peripheral T-cell malignancy with a markedly poor prognosis. The low prevalence of ATL among human T-cell leukemia virus type-1 (HTLV-1) carriers and the long latency period before ATL onset suggest that additional genetic lesions are required for ATL leukemogenesis. Recently, a large-scale genetic analysis clarified the entire picture of genetic alterations, identified a number of novel driver genes, and delineated their characteristics. Frequent alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Individuals infected with HTLV-1, including those with HAM, are at risk of developing ATL [33]. Those who have clonal expansion of HTLV-1-infected lymphocytes with ATL-related somatic mutations are at significantly high risk [34][35][36][37]. In this study, one slow progressor taking prednisolone developed ATL, and we retrospectively confirmed that this patient had such clones upon trial enrollment.…”
Section: Discussionsupporting
confidence: 60%
“…Individuals infected with HTLV-1, including those with HAM, are at risk of developing ATL [33]. Those who have clonal expansion of HTLV-1-infected lymphocytes with ATL-related somatic mutations are at significantly high risk [34][35][36][37]. In this study, one slow progressor taking prednisolone developed ATL, and we retrospectively confirmed that this patient had such clones upon trial enrollment.…”
Section: Discussionsupporting
confidence: 60%
“…More than a third of cases of ATLL show widespread hypermethylation of CpG islands. Methylation pathway genes ( TET2 , DNMT3 , EP300 and IDH2 ) are altered, but less frequently than in AITL 57 . Hypermethylation is one of the silencing mechanisms the MHC1 complex.…”
Section: Molecular Pathogenesis Of Ptcl Subtypesmentioning
confidence: 99%
“…Methylation pathway genes (TET2, DNMT3, EP300 and IDH2) are altered, but less frequently than in AITL. 57 Hypermethylation is one of the silencing mechanisms the MHC1 complex. Polycomb-dependent repression is enhanced in ATLL by trimethylation of histone lysine 27 and affects half the genes in ATLL.…”
Section: Adult T-cell Leukemia/lymphomamentioning
confidence: 99%
“…There is also evidence of an association between genetic biomarkers and ATLL; that is, the genetic profile of the host can contribute to prognosis and can be an important additional tool in the management of affected individuals if properly implemented in endemic areas 97 , 98 , 99 , 100 , 101 . This finding demonstrates the importance of implementing these approaches in our environment.…”
Section: Immunogenic Profile Of the Hostmentioning
confidence: 99%